A study of the drug tildrakizumab in psoriasis patients. (28th February 2020) - Reich, K.; Warren, R.B.; Iversen, L.; Puig, L.; Pau‐Charles, I.; Igarashi, A.; Ohtsuki, M.; Falqués, M.; Harmut, M.; Rozzo, S.; Lebwohl, M.G.; Cantrell, W.; et al.
Summary: Psoriasis is a common skin condition that causes red and scaly patches of skin. About 2% of people worldwide suffer from psoriasis. The authors of this study wanted to see how well the drug tildrakizumab treats psoriasis and the side effects it may have with long‐term use. In order to do so, they combined information from two clinical trials called reSURFACE 1 and reSURFACE 2. The authors examined the improvement of psoriasis symptoms using a scoring method named PASI (Psoriasis Area Severity Index) for a period of three years. This method grades the severity of a person's psoriasis and helps to measure any improvement. In clinical trials, success is measured by the proportion of patients who achieve a "PASI 75" or "PASI 90", which means a 75% or 90% reduction of the PASI score from the beginning of the treatment. Additionally, an excellent response to treatment can also be described by reaching a low PASI score such as a PASI score of less than 3 or less than 1 point. The authors found a high proportion of patients achieving an improvement in PASI during the first year that was well maintained with continued tildrakizumab 100 or 200 mg and, after three years, 80% and 60% of patients, respectively, achieved a PASI 75 and a PASI 90. Looking at PASI scores, 70% and 50% of patients, respectively, maintained a PASI score of less than 3 and less than 1, after three years. Even the patients who initially had a poor response (i.e. not much improvement) to tildrakizumab showed an improvement over time, if the treatment was maintained. Patients previously treated with etanercept (another drug for psoriasis) unsuccessfully, saw an improvement of their psoriasis with only two doses of tildrakizumab, with 80% and 40% of patients, respectively, achieving a PASI 75 and a PASI 90. Very few undesirable effects were seen, and no new or unexpected side effects were reported. The most frequent side effect was nasopharyngitis, which is commonly known as a cold. Severe infections, malignancies, or cardiovascular effects were uncommon and comparable to placebo (an inactive substance, like a "sugar pill"), indicating no increased risk of these events with tildrakizumab. In conclusion, tildrakizumab proved to be a good treatment for psoriasis for as long as three years, which is safe and has very few side effects. This is a summary of the study: Long‐term efficacy and safety of tildrakizumab for moderate‐to‐severe psoriasis: pooled analyses of two randomized phase III clinical trials (reSURFACE 1 and reSURFACE 2) through 148 weeks Abstract : Linked Article: Reich et al. Br J Dermatol 2020; 182 :605–617